Sustainable propulsion technology selection in penultimate mile delivery using the FullEX-AROMAN method - Bošković, Sara; Švadlenka, Libor; Jovčić, Stefan; Simic, Vladimir; Dobrodolac, Momcilo; Elomiya, Akram Elsaied (Elsevier Science Inc., 2024)
Sustainable transport is the priority for future cities and society. It is necessary to make sustainable urban transport policies to mitigate the harmful effects of current transportation systems. One of the essential issues in making cities cleaner is the propulsion technology of light commercial vehicles (LCVs). Most of the LCVs are compressed natural gas (CNG) and diesel-powered. However, cleaner, sustainable power sources, such as hydrogen, hybrid, solar, and electric have appeared in the market. This paper addresses the selection of propulsion technology for LCVs up to 3.5 tones for the Czech Post vehicle fleet. In this study, three main pillars are considered: economic, socio-environmental, and technical. Czech Post currently uses CNG-powered vehicles to transport shipments in penultimate mile delivery. The integrated FullEX-alternative ranking order method accounting for the two-step normalization (AROMAN) approach selects the best sustainable propulsion technology for the Czech Post vehicle fleet. The FullEX method identifies the criteria weights, while the AROMAN method ranks propulsion technologies. The results of the integrated approach reveal that the best propulsion technology for penultimate mile delivery is electrically powered, followed by hydrogen, hybrid, and CNG. A comparative analysis with other multi-criteria decision-making methods is also performed. The results confirm that the electrically powered solution is the best. The sensitivity analysis is carried out. The FullEX-AROMAN shows high resilience.
Udržitelný výběr technologie pohonu v předposlední míli pomocí metody FullEX-AROMAN
Keywords: Propulsion technology; Sustainability; Hydrogen; Multi-criteria decision-making; Penultimate mile delivery; FullEX; AROMAN; technologie pohonu; udržitelný; hydrogen; multikriteriální rozhodování; poslední míle; FullEX; AROMAN